Nine out of 10 sunbeds in England emit ultraviolet radiation levels that exceed current safety limits. (17th January 2013) - Tierney, P.; Ferguson, J.; Ibbotson, S.; Dawe, R.; Eadie, E.; Moseley, H.
Summary Background Exposure to ultraviolet (UV) radiation from sunlight is recognized as the principal cause of skin cancer. Moreover, sunbeds have been classified as carcinogenic by the International Agency for Research on Cancer. Despite this, there is a shortage of objective data on UV exposure levels in sunbeds in England. Objectives We set out to measure UV emission levels in sunbeds at sites around England, and to compare these levels with both current standards and natural sunlight. Methods Between October 2010 and February 2011, UV spectra were measured on site from a total of 402 artificial tanning units in England. Measurement instrumentation was calibrated, traceable to the National Physical Laboratory. Compliance with the relevant British and European standard was determined, and a skin‐cancer weighting factor was used to compare the carcinogenic potential of sunbeds with that of sunlight. Results For compliance with the European standard, erythemal‐effective irradiance should not exceed 0·3 W m−2. The values that we measured ranged between 0·10 and 1·32 W m−2 with a mean of 0·56 ± 0·21 W m−2. Only 10% of sunbeds surveyed were within the recommended limit. Application of the skin‐cancer weighting factor produced values that varied from 0·17 to 2·52 W m−2 with a mean of 0·99 ± 0·41 W m−2. The comparable value for Mediterranean noonday sun was 0·43 W m−2. Conclusions Nine out of 10 sunbeds surveyed throughout England emitted levels of UV radiation that exceed the maximum levels contained within the European standard. Moreover, the skin cancer risk for comparable times of exposure was up to six times higher than that for Mediterranean sunlight. This situation is unacceptable and stricter control measures must be put in place.